AN INNOVATIVE CONCEPTUAL MODEL FOR HUMAN RESOURCE MANAGEMENT IN EDUCATIONAL INSTITUTIONS BASED ON THE UTILIZATION OF DIGITAL TECHNOLOGY - Lumapouw, Harol Reflie; Rotty, Viktory Nicodemus Joufree; Sumual, Tinneke Evie Meggy (Ridwan Institute, 2024)
Educational institutions are faced with new challenges and opportunities in human resource management (HR). This research aims to develop an innovative conceptual model in HR management in educational institutions by utilizing digital technology. This model is expected to increase the effectiveness of the management of educators and education personnel by strengthening their digital capabilities and aiding their adaptation to the rapidly evolving digital landscape. The novelty of the research lies in the innovative approach that integrates digital technology in HR within educational institutions, creating a more dynamic, flexible, and collaborative work environment in the education sector, which is still rarely fully adopted. The research offers a novel approach by addressing the gap in the field of HR, where the integration of digital tools in HR is still underdeveloped. It provides a dynamic and flexible framework that can serve as a foundation for future HR strategies in education, contributing to the modernization and digital transformation of educational institutions.